Linking Urban Sustainability and Water Quality: Spatial Analysis of Topographic, Sociodemographic, and Flood-Related Factors Affecting Well Water in Jakarta (2017–2019) - Ashillah, Amanda Hana; Zakianis, Zakianis; Kusnoputranto, Haryoto; Fitratunnisa, Erni Pelita; Fauzia, Sifa; Lestari, Fatma; Shaw, Rajib; Adiwibowo, Andrio (Sustainability, 2025)
In 2019, well water was the primary source of clean water for 76.18% of Indonesian households. In the same year, based on an assessment of water quality in subdistricts in Indonesia, Jakarta had the third-lowest water quality index. This research aimed to analyze the impact of topographic, sociodemographic, and flood-related factors on well water quality in Jakarta from 2017 to 2019. This study employed an ecological design and used data obtained from various government agencies and has been published on an official website. Water quality data from wells in 261 subdistricts were analyzed using correlation and spatial analyses in this study. More than 83% of water well quality in Jakarta failed to meet the standard within the period of the study. The well water quality was the poorest in North Jakarta with the lowest elevation above sea level. The factors significantly associated with well water quality were low elevation (p ≤ 0.001), high population density (p = 0.015), and a low education level (p = 0.028). Local governments and private sectors should expand the piped water network and educate the public on well water quality and how to prevent waterborne diseases.